Preferences of Children's Religious Interfaith Marriages: Case Study in The International Conference on Religion and Peace (ICRP) - Rosdiana Rosdiana; Ahmad Bahtiar (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2020)
This research focuses on normative juridical aspects related to religious selection in children due to Interfaith Marriage (PBA). With the sociology of religion and the psychology of child development, this study looks at how the pattern of children’s education influences the tendency of the religious child's selection. Research informants are four PBA pairs taken randomly in the International Conference on Religion and Peace (ICRP) organization. The research findings explain that children's religious preferences follow their parents' path and parenting patterns who have different religions. In this study, there were at least three parenting practices applied by parents of interfaith marriages. First, parents of married couples of different religions teach two religious teachings at once. Secondly, one of the couples from interfaith marriages took over the child's religious education to follow their religion. Third, an agreement to make one child join each parent's religion. The pattern of nurture and religious environment applied by interfaith married couples to their children, related to religion, is very influential in the development of children's religious understanding. Religious education that is tolerant and understands religious plurality is a primary basis so that children are not trapped in psychological conflicts blaming one of their parents’ religions. This research is expected to contribute to family law development, particularly the law on protecting children.Penelitian ini memfokuskan pada aspek yuridis normatif terkait dengan kecenderungan pemilihan agama pada anak hasil Pernikahan Beda Agama (PBA). Dengan pendekatan sosiologi agama dan psikologi perkembangan anak, penelitian ini melihat bagaimana pola pendidikan anak yang berpengaruh terhadap kecenderungan pemilihan agama anak tersebut. Informan penelitian adalah empat pasangan PBA dalam lingkungan organisasi International Conference on Religion and Peace (ICRP) yang dipilih secara random. Temuan penelitian menjelaskan bahwa preferensi agama anak mengikuti alur dan pola pengasuhan kedua orang tua mereka yang berbeda agama. Hasil penelitian menunjukkan bahwa ada tiga pola asuh yang diterapkan oleh orang tua pernikahan beda agama. Pertama, orang tua dari pasangan nikah beda agama mengajarkan dua ajaran agama sekaligus. Kedua, salah seorang pasangan dari pernikahan beda agama mengambil alih pendidikan agama anak agar anak-anak mengikuti agamanya. Ketiga, kesepakatan untuk menjadikan salah satu anak ikut agama masing-masing orang tua. Pola pengasuhan dan lingkungan keagamaan yang diterapkan oleh pasangan nikah beda agama kepada anak-anak mereka, terkait dengan agama, sangat berpengaruh terhadap perkembangan pemahaman agama anak-anak. Pendidikan agama yang toleran dan memahami pluralitas agama menjadi basis dasar agar anak-anak tidak terjebak dalam konflik psikologis menyalahkan salah satu agama orang tuanya. Penelitian ini diharapkan memberikan sumbangsih bagi pengembangan hukum keluarga, khususnya hukum perlindungan terhadap anak.